Isolation and foaming functionality of acid-soluble protein from lupin (Lupinus angustifolius) kernels - Wong, A.; Pitts, K.; Jayasena, Vijay; Johnson, Stuart (John Wiley and Sons Inc., 2013)
Background: Australian sweet lupin (ASL) protein is conventionally isolated by alkaline extraction/acid precipitation, leaving a waste stream containing acid-soluble proteins (ASPs) and contaminating raffinose family oligosaccharides (RFOs). The foaming functionality of ASP isolated from ASL is not known, but ASP from another lupin species has demonstrated high foaming functionality. Results: Pre-soaking ASL kernels increased their protein/RFO ratio; however, some protein was lost by soaking. The foaming capacity of ASL protein isolated by different methods was ranked in the following order: alkaline extraction/isoelectric precipitation < direct acid extraction (novel ASP) < supernatant from isoelectric precipitation (conventional ASP) < ultrafiltered novel ASP = fresh egg white. Electrophoresis indicated enrichment of y-conglutin and albumin peptides in ASPs and of a single peptide in the fibre residue from alkaline extraction. Conclusion: The high foaming capacity of < ultrafiltered novel ASP, similar to that of fresh egg white, indicates the potential of this lupin protein as a food ingredient for foaming applications.